Living in Lisbon: How do we design? what can architects add? - Sequeira, M.; Adrião, J.; Gordon, R.; Mendonça, M. (Living in Lisbon: An architectural view on housing challenges, 2023)
The current housing crisis has generated a public debate around policies to tackle the increase in the price of homes, and ways in which The PRR (Plano de Recuperação e Resiliência/Recovery and Resilience Plan) can be executed to address the housing issue. The PRR aims to implement a set of reforms and investments to restore Portugal to sustained economic growth after the pandemic. Funded by the EU, it seeks to aid Portugal’s digital and ecological transition, and strengthen its economic and social resilience – including the construction of 26,000 dwellings by 2026. However, little has been said about the actual buildings that will materialise these policies and this plan, or the city we want to build from this operation. This conversation brings together architects committed to the construction of the contemporary city and intends to focus the discussion on a fundamental aspect of how operations of this kind are executed: architecture.